Tingkat Pengetahuan Mahasiswa Fakultas Farmasi Universitas Pekalongan Tentang Antibiotik - Fitri Nurul Hidayanti; Nila Oktaviani (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Limited information about antibiotics and information can only be used after a doctor's prescription, in which case their use is useless and causes resistance. Pharmacy students are expected to play a role as a catalyst to socialize antibiotic tolerance. The purpose of this study was to determine the antibiotic knowledge of students of the Faculty of Pharmacy, Pekalongan University. The study used descriptive analysis with stratified random sampling. The study population consisted of 554 pharmacy students, and a sample of 92 respondents who met the inclusion and exclusion criteria. Data analysis was carried out when the correct answer was given a score of 1 and the wrong answer was given a score of 0. He was then rated Good 76%-100%, Fair 56%-76%, and Less <56%. Based on the results of the research that has been completed, 74 people (80%), 18 people (20%) are classified as good knowledge in students of the Faculty of Pharmacy, Pekalongan University. They have a moderate category and no one is in the bad category. This shows that the majority of respondents have good information, namely 74 people out of 100 respondents.